2017
DOI: 10.1002/uog.16008
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular outflow tract obstruction in complicated monochorionic twin pregnancy

Abstract: Objectives Severe right ventricular outflow tract obstruction (RVOTO) is a potential complication in recipient twins of twin-to-twin transfusion syndrome (TTTS) that requires postnatal follow-up or treatment. We aimed to evaluate pregnancy characteristics of neonates with RVOTO from complicated monochorionic twin pregnancies, determine the incidence of RVOTO in TTTS cases and construct a prediction model for its development.Methods This was an observational cohort study of all complicated monochorionic twin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 34 publications
(54 reference statements)
3
32
3
Order By: Relevance
“…Initial mild RVOTO after birth is however important, as it may progress to severe RVOTO with need for intervention in infancy . The total incidence of postnatal RVOTO found in this study is slightly higher than in prior large cohort studies, which found an incidence of 2.1% to 4% . This can be explained by the systematic longitudinal follow‐up of all recipients in pregnancy, which allowed us to detect mild and late‐onset cases.…”
Section: Commentscontrasting
confidence: 58%
See 2 more Smart Citations
“…Initial mild RVOTO after birth is however important, as it may progress to severe RVOTO with need for intervention in infancy . The total incidence of postnatal RVOTO found in this study is slightly higher than in prior large cohort studies, which found an incidence of 2.1% to 4% . This can be explained by the systematic longitudinal follow‐up of all recipients in pregnancy, which allowed us to detect mild and late‐onset cases.…”
Section: Commentscontrasting
confidence: 58%
“…In untreated TTTS, approximately 10% to 12% of recipients will develop congenital heart disease, including RVOTO . Fetoscopic laser therapy is known to improve cardiac function, and the reported incidence of postnatal RVOTO in surviving recipients after laser therapy is 2% to 3% in larger series …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cardiac function usually improves within a few weeks after FLS, abnormalities of the pulmonary vasculature may persist despite complete laser surgery being performed, and this could lead to PPHN. As an analogy, right-ventricular outflow tract obstruction also occurs in recipients despite complete laser surgery and can result in abnormal development of the pulmonary valve and subsequent pulmonary stenosis or atresia [24]. In cases of incomplete laser surgery and the existence of residual anastomoses, the cardiac burden may be prolonged.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, knowledge of the presence of CSP should motivate the team to attempt to prolong the pregnancy as long as possible, as this baby has a relatively high likelihood of requiring a cardiac intervention shortly after birth. A recent study attempted to construct a predictive model for the development of RVOTO in cases of TTTS, and found that before laser surgery, those at increased risk had a pericardial effusion, an abnormal A wave in the ductus venosus, and earlier GA at surgery . We previously reported that the presence of both pulmonary valve dysplasia and pulmonary regurgitation that is classified as greater than “mild” for the recipient twin on FE before laser surgery indicates a sensitive marker (100%) for postnatal pulmonary valve disease; and if found postoperatively, adds specificity (89%) .…”
Section: Discussionmentioning
confidence: 99%